Pemanfaatan Blogger Web Design sebagai Media Informasi Digital dan Promosi Usaha Martabak Mahkota - Viola Rahmadani; Dila Kurnia; Sularno Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This study analyzes the promotional strategies and blog performance of Martabak Mahkota, a culinary business that uses the Blogger platform as a marketing tool. The research focuses on promotional content, operational time management, and the blog's interface for attracting customers. Results indicate that the "buy 10 get 1 free" promotion has the potential to increase order volume, but its effectiveness depends on the promotion's visibility, ease of ordering, and the quality of online content.